Growth of GaAs-based VCSEL/RCE Structures for Optoelectronic Applications via Molecular Beam Epitaxy - Somintac, A. S.; Estacio, E.; Bailon, M. F.; Salvador, A. A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
High intensity and sharp emission peaks, at light-hole (842 nm) and heavy-hole (857 nm) excitonic transitions for a 90 Å GaAs quantum well (QW) were observed for vertical-cavity surface-emitting laser (VCSEL) structure. Excellent wavelength selectivity and sensitivity were demonstrated by resonant cavity enhanced (RCE) photodetector at 859 nm, corresponding to the energy level of a 95 Å GaAs quantum well.